The Effect of Prediction Error on Belief Update Across the Political Spectrum. (June 2021) - Vlasceanu, Madalina; Morais, Michael J.; Coman, Alin
Making predictions is an adaptive feature of the cognitive system, as prediction errors are used to adjust the knowledge they stemmed from. Here, we investigated the effect of prediction errors on belief update in an ideological context. In Study 1, 704 Cloud Research participants first evaluated a set of beliefs and then either made predictions about evidence associated with the beliefs and received feedback or were just presented with the evidence. Finally, they reevaluated the initial beliefs. Study 2, which involved a U.S. Census–matched sample of 1, 073 Cloud Research participants, was a replication of Study 1. We found that the size of prediction errors linearly predicts belief update and that making large errors leads to more belief update than does not engaging in prediction. Importantly, the effects held for both Democrats and Republicans across all belief types (Democratic, Republican, neutral). We discuss these findings in the context of the misinformation epidemic.